2017
DOI: 10.1002/gps.4677
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lifelong cognitive lifestyle on executive function in older people with Parkinson's disease

Abstract: Cognitive reserve, although associated with global cognition, does not appear to be associated with executive function. This differential effect may reflect the specific cognitive profile of PD. The long-term effects of cognitive reserve on executive function in PD require further exploration. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The reported contrasting findings obtained in animals are not considerably more clarifying than the data provided by research in humans, which reports conflicting evidence about beneficial effects of enhanced experience on executive functions, when evaluated in different domains and pathological conditions (Darby et al, 2017; Hindle et al, 2017; MacPherson et al, 2019). At the current status of investigation, animal studies seem not significantly take advantage of the superior chance of variable and measure control in respect to the human studies.…”
Section: Discussionmentioning
confidence: 89%
“…The reported contrasting findings obtained in animals are not considerably more clarifying than the data provided by research in humans, which reports conflicting evidence about beneficial effects of enhanced experience on executive functions, when evaluated in different domains and pathological conditions (Darby et al, 2017; Hindle et al, 2017; MacPherson et al, 2019). At the current status of investigation, animal studies seem not significantly take advantage of the superior chance of variable and measure control in respect to the human studies.…”
Section: Discussionmentioning
confidence: 89%
“…Contrary to other domains, a relevant number of studies failed to establish a link between life experiences and a better performance in EF tasks. For instance, Hindle et al (2017) in a recent study reported no difference between high and low CR Parkinson Disease patients in tasks tapping EFs. However, a similar research of the same group, also on a PD sample, revealed that education promoted various cognitive functions including EFs ( Hindle et al, 2014 ), a pattern compatible to our data.…”
Section: Discussionmentioning
confidence: 95%
“…The studies on construct validity were of fair to good methodological quality, but the results indicate rather poor evidence of construct validity. In PD patients without cognitive impairment indicated by a MMSE score of 26 or higher, Hindle et al [64] found that the LEQ total score was positively associated with executive function. LEQ mid-life score was positively associated with mental generativity, assessed through verbal fluency (word generation after letter- and category cues; r = 0.25, p<0.05), design fluency (novel design generation by connecting dot arrays with 4 straight lines; r = 0.26, p<0.05), tasks and set shifting and switching (Test of Everyday Attention Elevator Counting; r = 0.25, p<0.05).…”
Section: Resultsmentioning
confidence: 99%